Increased Levels of The Hormone Prolactin Through Complementary Treatments (Breast Care) and Spiritual Approaches (Qur'anic Murottal) - Ahmad, Mardiana; Katili, Tressan Eka Putri S.; Arsyad, Nur Aliya; Riyandani, Rika; Juwita, Juwita; Sukarta, Asma (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Breast milk is the best natural nutrition for babies and is needed during the first six months of a baby's life. Breast care and Al-Quran Murottal are methods for increasing prolactin hormone levels, and can also reduce the release of stress hormones, which are very important when mothers are breastfeeding. Quasi-experimental (quasi-experiment) with the approach used is a pre-test post test control group design, namely, research that uses a control group to be used as a comparison between pretest and posttest. The sample was obtained using a purposive sampling technique with a total of 39 postpartum mothers divided into (13 postpartum mothers in the breast care group, 13 postpartum mothers in the Murottal Al-Quran group, and 13 postpartum mothers in the control group). Prolactin hormone levels were measured before and after treatment. Data were analyzed using paired t-test and linear regression. The results showed that the breast care group had a value of p= 0.007<0.05, the Al-Quran mental group had a value of p=0.011<0.05, and the control group had a value of p=0.154>0.05. showed that the breast care group and Al-Quran murotal had an influence on prolactin hormone levels, whereas the control group had no influence on prolactin hormone levels. In conclusion, Breast Care and Murottal Al-Quran can be used to increase prolactin hormone levels in postpartum mothers so that postpartum mothers do not need to be confused about how to increase breast milk production.